2013
DOI: 10.1016/j.apsoil.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Addition of activated switchgrass biochar to an aridic subsoil increases microbial nitrogen cycling gene abundances

Abstract: a b s t r a c tIt has been demonstrated that soil amended with biochar, designed specifically for use as a soil conditioner, results in changes to the microbial populations that reside therein. These changes have been reflected in studies measuring variations in microbial activity, biomass, and community structure. Despite these studies, very few experiments have been performed examining microbial genes involved in nutrient cycling processes. Given the paucity of research in this area, we designed a 6 month st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
70
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(85 citation statements)
references
References 43 publications
10
70
0
4
Order By: Relevance
“…In accordance with Ducey et al (2013), no significant correlation between the abundance of AOA and AOB and soil biochar amendment was found in this study (Figure 2b). However, independent of the amount of biochar added the AOA/AOB gene ratio increased over time in all microcosms (Figure 3b).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In accordance with Ducey et al (2013), no significant correlation between the abundance of AOA and AOB and soil biochar amendment was found in this study (Figure 2b). However, independent of the amount of biochar added the AOA/AOB gene ratio increased over time in all microcosms (Figure 3b).…”
Section: Discussionsupporting
confidence: 70%
“…Several studies have documented that biochar induces shifts in the microbial community composition (Rondon et al, 2007;Steinbeiss et al, 2009;Anderson et al, 2011;Khodadad et al, 2011;Ducey et al, 2013), whereas other studies described that the addition of biochar to soils does affect soil N 2 O emissions (Yanai et al, 2007;Singh et al, 2010b;Taghizadeh-Toosi et al, 2011;Felber et al, 2012;Cayuela et al, 2013). However, a potential link between the observed shifts in microbial community composition and the decreased soil N 2 O emissions has not been subject of systematic investigation so far.…”
Section: Introductionmentioning
confidence: 90%
“…In previous studies, at DNA level, biochar has been shown to increase both archaeal amoA and bacterial amoA compared to control at the last wet cycle of an incubation. 27 Correspondingly, Ducey et al 25 observed a higher bacterial amoA abundance in the presence of biochar at the end of an incubation of 6 months. In this experiment, no fertilizer was added, and ammonium is likely derived from the mineralization of organic matter, to which AOA is more adapted, 57,58 resulting in no effect on bacterial amoA transcription by biochar.…”
Section: ■ Experimental Sectionmentioning
confidence: 96%
“…Biochar is a carbonaceous material produced by pyrolysis of biomass in a limited oxygen condition (Schahczenski 2010). Numerous studies showed that adding biochar into infertile soils can potentially increase the cation exchange capacity of the soil and nutrient sorption (Jien and Wang 2013;Gray et al 2014); stimulate soil microorganisms activities (Ducey et al 2013), and reduce plant nutrients leaching losses from the soil (Kameyama et al 2012). Moreover, several studies have highlighted the positive effects of biochar on root growth (Ogawa and Okimori 2010;Prendergast-Miller et al 2014), particularly increased root biomass (Xiao et al 2016) and root length (Solaiman et al 2012;Olmo et al 2016).…”
Section: Introductionmentioning
confidence: 99%